Identification of Misconceptions on Material of Food Digestive System in Humans Using Two Tier Multiple Choice Diagnostic Tests at SMPN 15 Padang - Fahry Harahap; Rahmawati Darussyamsu; Elsa Yuniarti; Ristiono Ristiono (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Misconceptions is a concept that doesn’t suitable with the concept recognized by expert. Misconceptions whom occur in students’ selves prohibit the formed of relation with new concepts and disrupt the realization of learning process. Therefore, misconceptions needs to be known by teacher and folloed up early. The aim of this research is to identify the misconception on the concepts of food digestive system material in humans which experienced by second class at SMP 15 Padang. This research is a descriptive research which conducted at SMP 15 Padang. The populations of this research are 221 students of second class. The sample is 22,5% of 221 members of populations, which is 50 members.the tacking of sampling used simple random sampling technique. The data used are primary data which taking by two tier multiple choice and analyzed through quantitative technique analysis by percentage.         Based on the results of the study, it seen that the highest misconception is the type of food ingredients and its content by 38%, digestive organs (digestive glands and glands) by 49%, the structure and function of the digestive organs by 38%, the relationship between structure and bioprocess in digestive organs by 46.75%, indicator of mechanical and chemical digestion by 50%, disorders / diseases of the digestive system by 49%, and the Thus it can be concluded that there is a misconception in Class VIII students of SMP 15 Padang about the food digestive system material in humans with varying percentages.